2006
DOI: 10.1111/j.1365-3040.2006.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

O3 impacts on plant development: a meta‐analysis of root/shoot allocation and growth

Abstract: The mechanism of O 3 action on plants remains poorly characterized. Symptoms include visible lesions on the leaf surface, reduced growth and a hypothesized reduction in allocation of carbohydrate to roots. The generality of this latter phenomenon has not been demonstrated. Here, a meta-analysis is performed of all available experimental data, to test the hypotheses that O 3 exposure of the shoot inhibits biomass allocation below ground (the root/shoot allometric coefficient, k ) and inhibits whole-plant growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 145 publications
12
106
1
Order By: Relevance
“…A quantitative metaanalysis showed that the root/shoot ratio was significantly reduced by elevated ozone concentration, indicating greater sensitivity of root biomass to ozone (Wittig et al, 2009). The lower leaves act as preferential sources of assimilate for roots, and the upper leaves for shoots; as ozone has greater effects on older, lower leaves than on younger, less exposed leaves, ozone-accelerated senescence in the lower canopy could contribute to reduce allocation to roots, and thus to the lower root/shoot ratio (Grantz et al, 2006). The total biomass of clone 546 decreased more than that of clone 107.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative metaanalysis showed that the root/shoot ratio was significantly reduced by elevated ozone concentration, indicating greater sensitivity of root biomass to ozone (Wittig et al, 2009). The lower leaves act as preferential sources of assimilate for roots, and the upper leaves for shoots; as ozone has greater effects on older, lower leaves than on younger, less exposed leaves, ozone-accelerated senescence in the lower canopy could contribute to reduce allocation to roots, and thus to the lower root/shoot ratio (Grantz et al, 2006). The total biomass of clone 546 decreased more than that of clone 107.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity among levels of these categorical variables was assessed by re-sampling following Adams et al (1997). For multiple comparisons, groups were considered to differ significantly if their 95% confidence intervals did not overlap, providing a conservative test of group differences (Feng et al, 2008;Grantz et al, 2006;Morgan et al, 2003;Taub et al, 2008). Each categorical level for all crops was included in this analysis if there were at least two papers and five observations.…”
Section: Meta-analysesmentioning
confidence: 99%
“…In this short-term study 286 there were larger effects on roots than above ground biomass for birch as has previously been 287 reported for several species including trembling aspen (Populus tremuloides, Coleman et al 288 1996) and birch (Betula pendula; Riikonen et al 2004). This could be evidence of reduced 289 partitioning to roots, however, it has been shown that for trees the main source of photosynthate 290 for the roots is from the lower leaves, and it is these older leaves that tend to be most affected as 291 a consequence of ozone exposure (Grantz et al 2006). Therefore, it is possible that further 292 reductions in partitioning to roots may have occurred if the exposure had occurred over a longer 293 timescale, although subsequent root re-growth after relief from a period of ozone stress may 294 occur for some species.…”
Section: Total Biomass 244mentioning
confidence: 99%
“…Some studies have 59 indicated that a change in biomass partitioning can occur in response to ozone, for example, a 60 decrease in the dry mass of roots and branches of Betula pendula attributed to ozone has been 61 shown at the end of the exposure (Riikonen et al 2004). It is thought that decreased partitioning 62 to the roots may occur with increasing ozone exposure because the mature, lower leaves act as 63 the main source of assimilate for root growth, and these are frequently the most damaged by 64 ozone (Grantz et al 2006, Cooley and Manning 1987, Okano et al 1984 alder. All plant material was oven-dried at 65°C for a minimum of seven days before weighing.…”
mentioning
confidence: 99%